Наша Родина - Россия - Шуйская Юлия Викторовна (Эксмодетство, 2017)
Экземпляры: ф.6 (20190830) / Инвентарный номер: 3278zzz / Цена: / Сис.шифр: 26.89(2Рос) / Авт.знак: Ш 95 / ГРНТИ: 39.23 / ББК: 26.89(2Рос)я2